EDUKASI KONSUMSI TABLET TAMBAH DARAH UNTUK PENCEGAHAN ANEMIA REMAJA PUTRI DI SMA NEGERI 1 KARANGNONGKO - Salsabila Suryaningrum (WASATHON Jurnal Pengabdian Masyarakat, 2026)
Anemia remains a common health problem among adolescent girls due to increased iron requirements during the growth period and blood loss during menstruation. Poor adherence to Iron Supplement Tablet (IST) consumption is one of the factors contributing to the increased risk of anemia. This community service program aimed to improve adolescent girl’s knowledge and awareness of the importance of IST consumption as an effort to prevent anemia. The program involved 30 female students from SMA Negeri 1 Karangnongko and was conducted throught health education using PowerPoint presentations, posters, leaflets, interactive discussions, question and answer sessions, and educational games. The effectiveness of the program was evaluated using pre-test and post-test asessements, followed by the Wilcoxon signed-rank test. The results showed that the mean knowledge score increased from 92.67 to 94.67, although the improvement was not statistically significant (p=0.574). Nevertheless, the program successfully strengthened participant’s understanding and increased their awareness of the importance of regular IST consumption as a strategy to prevent anemia among adolescent girls.